Л. М. Толстой і родина Вернадських - Лавров, В.В. (Культура народов Причерноморья, 2005)
Зі щоденника В. І. Вернадського, архівних та мемуарних матеріалів відновлюються особисті контакти сім'ї вченого з Л. М. Толстим у кінці ХІХ - початку ХХ ст.. У статті висвітлюється провідна роль Л. М . Толстого в духовному піднесенні російської інтелігенції 1880-х років, а також дається характеристика В. І. Вернадського як уважного читача творів Л. М. Толстого. На основе дневниковых записей В. И. Вернадского, архивных и мемуарных материалов восстанавливаются личные контакты семьи В. И. Вернадского с русским писателем Л. Н. Толстым в к. ХІХ - начале ХХ вв. В статье показана решающая роль Л. Н. Толстого в духовном становлении русской интеллигенции 1980-х годов, а также дается характеристика В. И. Вернадского как внимательного и глубокого читателя произведений Л. Н. Толстого. Вводятся новые источники и архивные материалы. On the basis of diary notes of V.I. Vernadsky, archival materials and memoirs materials personal contacts of V.I. Vernadsky family with Russian writer L.N. Tolstoy at the end of XIX century - beginning of XX century are being restored. The article represents key role of L.N. Tolstoy in the spiritual formation of Russian intelligentsia of 1880-ies and it is also represents description of V.I. Vernadsky as a careful and thorough reader of L.N. Tolstoy works. New literature, which was earlier unknown, about contacts of V.I. Vernadsky family with famous writers is introduced. For the first time we start using new archival materials.